Non-Syndromic Multiple Keratocystic Odontogenic Tumor: A Case Report - Sohanian Shabnam; Seifi Safoura; Kouchak Dezfouli Mohammad; Kiani Marjan; Khakbaz Oveys (Journal of Otolaryngology Advances, 2017)
A Keratocystic Odontogenic Tumor (KCOT) is a benign odontogenic lesion that is well-known for its histopathological features and invasive clinical behaviors. KCOTs may be non-syndromic or syndromic, and the syndromic type presents a higher risk of recurrence and invasive behaviors. Non-syndromic KCOTs are uncommon and account for only 5% of the cases. The purpose of the present case report is to conduct clinical, radiographic and pathologic evaluations and treat a 37-year-old man with non-syndromic nevoid basal cell carcinoma. Syndromic and non-syndromic keratocysts present more invasive behaviors than the solitary type. The initial symptoms of syndromic keratocysts appear as multiple keratocysts of the mandible and maxilla that are diagnosed by a dentist; as a result, the diagnosis and treatment of the disease is very crucial.
Keywords: KCOT